Influencia de la catastrofización del dolor en el afrontamiento en adultos con dolor crónico. (Salud, Arte y Cuidado, 2025)
Introduction: Pain alters coping strategies, and catastrophizing may be a triggering factor, as it represents a pattern of negative and exaggerated thinking, exacerbating the experience and making effective coping more difficult. There are gaps in understanding the specific mechanisms, moderating factors, and long-term effects related to pain. Additionally, there is potential for innovation through personalized approaches, advanced technologies, and biopsychosocial models. Objective: To determine the explanatory percentage of pain catastrophizing on coping in adults living with chronic pain. Materials and Methods: Correlational-explanatory design, with a convenience sample of 89 adults living with chronic pain. A personal data form, the Pain Catastrophizing Scale (α=.94), and the Pain Coping Questionnaire (α=.88) were used. The results were analyzed using descriptive and inferential statistics (Spearman's correlation, linear regression model). Results: Most participants were women, with an average age of 50.9 years. Higher levels of catastrophizing were associated with greater coping (p
Keywords: catastrophism; psychological adaptation; chronic pain; adult